Endolyn (CD164) modulates the CXCL12-mediated migration of umbilical cord blood CD133+ cells. - Forde, S; Tye, B; Newey, S; Roubelakis, M; Smythe, J; McGuckin, C; Pettengell, R; Watt, S (2007)
Hematopoietic stem cell/hematopoietic progenitor cell (HSC/HPC) homing to specific microenvironmental niches involves interactions between multiple receptor ligand pairs. Although CXCL12/CXCR4 plays a central role in these events, CXCR4 regulators that provide the specificity for such cells to lodge and be retained in particular niches are poorly defined. Here, we provide evidence that the sialomucin endolyn (CD164), an adhesion receptor that regulates the adhesion of CD34+ cells to bone marrow stroma and the recruitment of CD34+CD38(lo/-) cells into cycle, associates with CXCR4. The class II 103B2 monoclonal antibody, which binds the CD164 N-linked glycan-dependent epitope or CD164 knockdown by RNA interference, significantly inhibits the migration of CD133+ HPCs toward CXCL12 in vitro. On presentation of CXCL12 on fibronectin, CD164 associates with CXCR4, an interaction that temporally follows the association of CXCR4 with the integrins VLA-4 and VLA-5. This coincides with PKC-zeta and Akt signaling through the CXCR4 receptor, which was disrupted on the loss of CD164 though MAPK signaling was unaffected. We therefore demonstrate a novel association among 3 distinct families of cell-surface receptors that regulate cell migratory responses and identify a new role for CD164. We propose that this lends specificity to the homing and lodgment of these cells within the bone marrow niche.